Javan Surili : A Survey Population and Distribution in Mt. Slamet Central Java, Indonesia - Arif Setiawan; Yohannes Wibisono; Tejo Suryo Nugroho; Ika Yuni Agustin; Mohamad Ali Imron; Satyawan Pudyatmoko; Djuwantoko . (Jurnal Primatologi Indonesia, 2010)
Abstrak. Survei ini adalah penilaian yang pertama terhadap populasi dan distribusi surili jawa (Presbytis fredericae) di Gunung Slamet, Jawa Tengah, Indonesia. Survei telah dilakukan selama 150 hari di hutan pegunungan dan menyusuri jalur-jalur yang ada sepanjang 125,38 km. Survey ini telah mencatat 233 individu dari 54 kelompok monyet surili. Metode garis transek telah diterapkan dalam survey ini dan estimasi kerapatan surili jawa adalah 5,6 – 8,16 individu/km2, yang menempati  198.68 km2 potensial habitat. Estimasi populasi surili jawa di Gunung Slamet kurang lebih 1172 – 1621 individu. Perburuan, penebangan liar, pengumpulan kayu bakar, perburuan tanaman hias adalah ancaman yang menyebabkan degradasi habitat surili jawa di hampir semua lereng gunung. Ini adalah sub-populasi terbesar yang tersisa di jawa tengah, jadi perlindungan terhadap Gunung Slamet adalah sangat penting untuk menyelamatkan populasi monyet dan habitatnya, sebagaimana kita ketahui bahwa  distribusi sub-species Presbytis di jawa tengah tidak terdapat di dalam kawasan konservasi. Peningkatan status perlindungan hutan, penegakan hukum, program kesadaran konservasi, pemberdayaan komunitas harus didukung dan diteruskan di Gunung Slamet.Abstract. This survey is the first assessment of the population and distribution of the Javan surili  (Presbytis fredericae) on Mt.Slamet, Central Java, Indonesia. The survey was carried out for a total of 150 days in the mountainous forest, while walking 125.38 km along existing trails. There were 233 individuals recorded, belonging to 54 groups of monkeys. The line transect method was applied during the survey and it was estimated that there were 5.6 up to 8.16 individuals/km2  density of Javan surili, occuping 198.68 km2, indicating a possible potential habitat. The population of the Javan surili on Mt.Slamet was estimated at approximately 1172 – 1621 individuals. Hunting, illegal logging, fuel wood collection, ornamental forest plants gathering were threats which were the cause of massive degradation of the Javan surili habitat across the facing slope. With its largest sub-population remaining in Central Java,  protecting the Mt. Slamet is urgently needed to save this monkey population and its habitat, as it is known that there is no conservation area in the range distribution of Presbytis subspecies in Central Java.  Increasing the forest protection status, law enforcement, conservation awareness programs, and community based empowerment should be supported and continued in Mt. Slamet.Key words: rekrekan, surili, Mt.Slamet, population,  distribution, endangered